Variasi Sapaan Anak Perempuan dalam Bahasa Banjar - Elisa, Nova (Jurnal Cahaya Edukasi, 2025)
Abstrak—This study aims to describe the variations in form, meaning, and social function of greetings for girls in the Banjar language based on the speech practices of three informants from the Banjar Kuala and Banjar Hulu regions. Using a descriptive qualitative approach, data were collected through semi-structured interviews and analyzed using an interactive analysis model. The results of the study show at least twelve forms of greetings used, including galuh/aluh, gadis, nak, cu, ading, as well as affective greetings such as si bungas and si pintar. These variations reflect the values of politeness, family intimacy, and positive expectations for girls. The choice of greetings by informants is influenced by social context, family customs, and personal preferences. These findings are in line with Brown and Levinson’s concept of positive politeness and Chaer’s theory of social relations in the greeting system, and are supported by research by Kurniawati et al. On greetings in the family socialization process. However, the findings of this study are not intended to generalize the entire Banjar community, given the limited number of informants and the local context. This study provides an initial overview of the dynamics of female children’s greetings in Banjar culture and can serve as a basis for further studies involving more regions and informants.